STELLAR WIND IN THE ISM - Lozinskaya, T. A. (Одеські астрономічні публікації, 2017)
After a brief review of the modern understanding of stellar wind's action on the ISM we consider two aspects of its "global" collective effect from observational viewpoint. First, stellar winds from OB associations do provide favorable conditions for triggering star formation. Second, the entire history of an active star-forming complex does regulate the nature of a wind-blown bubble or a SNR.